THE ADAPTIVE CAPACITY OF YOUNG MIGRANTS FROM KYRGYZSTAN IN MOSCOW - `OSADCHAYA, Galina; KIREEV, Egor; KISELEVA, Evgenia; CHERNIKOVA, Anna (CENTRAL ASIA AND THE CAUCASUS, 2021)
The significant numbers of migrants from Kyrgyzstan in Moscow and the difficulties in adapting to the new conditions recorded by our research highlight the need to explore the adaptive capacity of young Kyrgyz. The lack of scientific knowledge about the potential adaptive capacities of different groups of young Kyrgyz hinders the creation of optimal conditions that would allow them to internalize norms, values, and rules of behavior, increases the potential for conflict in the Moscow community, makes the life of migrants less comfortable, and complicates integration processes in the Eurasian Economic Union (EAEU). The purpose of this study is to characterize the adaptive capacity of young people from Kyrgyzstan in Moscow that helps them